The Impact of Elementary Students' Attitudes Toward Online Learning on Memory Retention and Comprehension During the COVID-19 Pandemic: An Exploratory Study in Yogyakarta, Indonesia - Munastiwi, Erni; Marpuah, Siti (MyResearch ID Publishing, 2024)
Purpose – This study aims to investigate elementary school students' attitudes toward online learning during the COVID-19 pandemic, focusing on the relationship between their attitudes and cognitive outcomes such as memory retention and comprehension. The goal is to enhance understanding of how psychological factors influence the effectiveness of online education and contribute to strategies for improving educational practices in remote environments. Methods/Design/Approach – An exploratory research design was employed, using a structured survey distributed to 906 students from eight elementary schools in Yogyakarta, Indonesia. Data were collected through online questionnaires assessing attitudes toward online learning, memory retention, and comprehension abilities. Descriptive statistics and Pearson’s correlation coefficient were used to analyze the data, identifying relationships between students' attitudes and cognitive outcomes. Findings – The study found that 52.65% of students had a negative attitude towards online learning. Students with positive attitudes exhibited better memory retention and comprehension, while those with negative attitudes showed significant challenges in these areas. The relationship between attitude and memory retention was statistically significant (χ² = 71.619, p < 0.001), as was the relationship between attitude and comprehension (χ² = 143.686, p < 0.001). Originality/Value – This research adds to the limited studies on the psychological impact of online learning on younger students, offering insights into how attitudes shape cognitive performance in remote education environments. It emphasizes the importance of fostering positive attitudes to improve educational outcomes in online settings. Practical Implications – The findings suggest that educational interventions should focus on improving students' attitudes towards online learning to enhance cognitive engagement and performance. Incorporating blended learning models and more interactive, engaging online experiences could better support young learners in remote education environments. Keywords Online learning, elementary education, attitudes, memory retention, comprehension. Paper type Research paper